Interpretation of Subsurface Geological Structure and Modeling Geothermal System of Bur Ni Telong Area Based on Gravity Anomaly Data - MARVITA (NIM: 22316009), YURDA
Mount Bur Ni Telong of Bener Meriah, Aceh is one of the areas traversed by the volcanic arc of the Bukit Barisan and located in the Southern part of Mount Bur Ni Geureudong. Mount Bur Ni Telong area has geothermal sources which are characterized by the presence of hot springs and fumaroles. In order to obtain the information about the Bur Ni Telong geothermal prospect areas, the aim of this research is to develop a subsurface structure model of the geothermal system by using gravity data. In this research, the interpretation of the structure and the subsurface geological modeling were carried out using complete Bouguer anomaly and residual anomaly data which is supported by geological information and other supporting data. Analysis of structures and subsurface modeling identified faults with SW – NE and NW – SE trends in the Bur Ni Telong geothermal prospect areas. These faults are estimated to be a fault that controls the manifestation in the area. Furthermore, there are geothermal prospect areas that represented by low density in the Northeast part of Mount Bur Ni Telong. This area is indicated as reservoir zone or hydrothermal fluids carrier layer from the heat source of Mount Bur Ni Telong.